Bihar Third Five Year Plan Progress Report for the Period Ending December, 1961 - Planning Commission (Planning Commission, 1961)
Heads of Development, Agriculture and C.D, Irrigation and Power, Industry and Mining, Transport and Communication, Miscellaneous.
Bihar Progress Report